ESTIMATION OF CARBONDIOXIDE PARTIAL PRESSURE DISTRIBUTION (PCO2) AND PH IN SIRE BAY. NORTH LOMBOK - Nadhif Arsyad S, Mochammad
The partial pressure of CO2 (pCO2) in the ocean plays an important role in the process of transfer or flow of CO2 from the atmosphere to the sea and vice versa, so the accuracy of calculating the partial pressure of ocean CO2 is needed. This research was conducted to examine the parameters of sea surface temperature (T), salinity (S), and chlorophyll-a (K) to estimate the partial pressure of carbon dioxide (pCO2) and pH of sea air in Sire Bay, North Lombok from field data. The data used in this study is the data model of PCO2 empirical equilibrium development and pH obtained from measurements in the field in a joint study of LIPI on July 21st, 2019 and October 21st in 2018. The formation of this study uses field data using multiple linear regression methods. From the research results obtained from empirical estimates of the value of marine pCO2 are as follows: pCO2 = -588.089 + 35.649(T) – 2.619(S) + 2.190(K) and the statistical estimation of the marine pH value as follows: pH = 46.094 – 1.345(T) – 0.129(K) and pH = 17.419 – 0.0284(pCO2).